Analysis of artistic discourse according to modern trends in thinking Model art (Journal of the College of Basic Education, 2022)
Recent trends in thinking emphasize the need for the recipient to acquire skills that enable him to analyze the artwork by producing mental images through which he can engage with the creative artistic discourse (the painting), which would reduce the complexity of the cognitive structure of the work itself, especially as we live in an era of cognitive openness.